Catheter ablation of atrial fibrillation in patients with hypertrophic cardiomyopathy: a European observational multicentre study. Issue 9 (30th April 2021) - Creta, Antonio; Elliott, Perry; Earley, Mark J; Dhinoja, Mehul; Finlay, Malcolm; Sporton, Simon; Chow, Anthony; Hunter, Ross J; Papageorgiou, Nikolaos; Lowe, Martin; Mohiddin, Saidi A; Boveda, Serge; et al.
Abstract: Aims: Atrial fibrillation (AF) is common in hypertrophic cardiomyopathy (HCM). Data on the efficacy of catheter ablation of AF in HCM patients are sparse. Methods and results: Observational multicentre study in 137 HCM patients (mean age 55.0 ± 13.4, 29.1% female; 225 ablation procedures). We investigated (i) the efficacy of catheter ablation for AF beyond the initial 12 months; (ii) the available risk scores, stratification schemes and genotype as potential predictors of arrhythmia relapse, and (iii) the impact of cryoballoon vs. radiofrequency in procedural outcomes. Mean follow-up was 43.8 ± 37.0 months. Recurrences after the initial 12-month period post-ablation were frequent, and 24 months after the index procedure, nearly all patients with persistent AF had relapsed, and only 40% of those with paroxysmal AF remained free from arrhythmia recurrence. The APPLE score demonstrated a modest discriminative capacity for AF relapse post-ablation ( c -statistic 0.63, 95% CI 0.52–0.75; P  = 0.022), while the risk stratification schemes for sudden death did not. On multivariable analysis, left atrium diameter and LV apical aneurysm were independent predictors of recurrence. Fifty-eight patients were genotyped; arrhythmia-free survival was similar among subjects with different gene mutations. Rate of procedural complications was high (9.3%), although reducing over time. Outcome for cryoballoon and radiofrequency ablation was comparable. Conclusion: Very late AF relapses post-ablation is common in HCM patients, especially in those with persistent AF. Left atrium size, LV apical aneurysm, and the APPLE score might contribute to identify subjects at higher risk of arrhythmia recurrence. First-time cryoballoon is comparable with radiofrequency ablation.